Unique cardiac involvement in a patient with squamous cell lung cancer - Alwakeel, Ragad A.; Almutairi, Nora S.; Almutairi, Sara S.; Sulaimani, Ihab (International Journal Of Community Medicine And Public Health, 2025)
Cardiac metastasis from lung tumors is rare, and often asymptomatic, making diagnosis challenging. Herein this report presents a case of a 69-year-old male with squamous cell carcinoma of the lung with cardiac metastasis to the left ventricle. Two days post chemotherapy, he developed symptoms of chest pain and mild hemoptysis. An electrocardiogram revealed ST-segment elevation in the inferior leads, suggesting a possible inferior ST-segment elevation myocardial infarction (STEMI). His symptoms improved with Nitroglycerin, and prescribed calcium channel blockers, and long-acting nitrates. The symptoms were confirmed to be attributed to an atherosclerotic plaque. This case highlights the challenge of differentiating between coronary artery disease and cardiac symptoms, and emphasizes the necessity of thorough investigation in cancer patients with cardiac symptoms.